2002
DOI: 10.21273/jashs.127.2.165
|View full text |Cite
|
Sign up to set email alerts
|

Thinning `Fuji' Apple Blossoms with Synthetic Auxins (MCPB-ethyl or NAA) and Ethephon with or without Postbloom Thinning with Carbaryl

Abstract: Three experiments were conducted at two locations, two at Summerland, British Columbia, Canada and one at Corvallis, Ore., to evaluate synthetic auxins (MCPB-ethyl or NAA) and ethephon as blossom thinners for `Fuji' apple [Malus sylvestris (L.) Mill var. domestica (Borkh.) Mansf.]. These experiments also involved application of carbaryl at 1000 mg·L-1 in the postbloom period. All blossom thinners were sprayed at 85% full bloom w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…This result agrees with previous reports where the application of different commercial auxins did not affect the firmness of pepper (Lopez-Elias et al, 2005;Salas et al, 2009), although in other species, e.g. apple (Guak et al, 2002;Curry (2006) and kiwifruit (Bregoli et al, 2006), hormones have been reported to increase fruit firmness. By contrast, in stone fruit species, e.g.…”
Section: Discussionsupporting
confidence: 93%
“…This result agrees with previous reports where the application of different commercial auxins did not affect the firmness of pepper (Lopez-Elias et al, 2005;Salas et al, 2009), although in other species, e.g. apple (Guak et al, 2002;Curry (2006) and kiwifruit (Bregoli et al, 2006), hormones have been reported to increase fruit firmness. By contrast, in stone fruit species, e.g.…”
Section: Discussionsupporting
confidence: 93%
“…For many other tree fruit species, crop load is managed by blossom-and post bloom thinning agents to improve fruit quality and reduce fruit number and total sink demand per tree (Westwood, 1993). Indeed, improvements in apple fruit quality (Guak et al, 2002;Lakso et al, 2001) and value (Marini, 2002;Stover et al, 2001) in response to chemical thinning have been reported. Similar results have been reported for peach (P. persica) (Genard et al, 1999;Miranda-Jimenez and Royo-Diaz, 2002).…”
mentioning
confidence: 99%
“…In previous studies, field trials using synthetic auxin analog NAA for the treatment of apple trees did not support the theory of inhibitory effect of auxins on flower bud initiation. Spraying of apple trees with NAA did not reveal negative effects of this compound on return bloom ( Guak et al. 2002 ).…”
Section: Discussionmentioning
confidence: 99%
“…2013 , Stopar 2010 , Zabrkić et al. 2011 ) or did not significantly affect return bloom of the experimental trees ( Guak et al. 2002 ).…”
Section: Introductionmentioning
confidence: 87%